Influence of Seed Priming on Germination and Seedling Vigour of Wood Apple (Feronia limonia Swingle) - Sau, Sayan; Pal, Binayak; Sarkar, Sukamal; Sarkar, Tanmoy (International Journal of Bio-resource and Stress Management, 2019)
The present experiment was conducted to study the influence of seed priming treatments on germination and seedling vigour of wood apple (Feronia limonia Swingle) at Horticulture experimental and learning unit, Faculty of Horticulture, Bidhan Chandra Krishi Viswavidyalaya, Mohanpur, Nadia, West Bengal, India (22°5643''N, 88°32'03 ''E and 397 m above mean sea level) during December to June of 2016-2017. The treated seeds were raised on polythene bags under shade net house (covered with 200-micron thickness polythene shade net) condition to avoid climatic irregularities. The experiment was laid out in a completely randomized design comprising eight treatments (GA3 50 ppm and 100 ppm, KNO3 50 ppm and 100 ppm, Thiourea 50 ppm and 100 ppm, water soaking, and directly sown seed i.e. control) and replicated for five times. The result of the present investigation revealed that amongst the different concentrations of used chemicals, GA3 100 ppm was most efficient to ensure the maximum germination percentage (81.67%) which was 96.01% higher than the control. Similar trend of obtaining highest values from GA3 treated seed on most of the seedling growth parameters was also observed such as highest seedling height (442.23 mm), shoot (2.51 mm) and root diameter (3.22 mm), leaf number (12.00), seedling fresh (2.14 g) and dry weight (1.01 g), leaf chlorophyll content [chlorophyll a (78.51 mg g-1 FW), chlorophyll b (98.70 mg g-1 FW) and total chlorophyll (135.70 mg g-1 FW), respectively] and leaf nitrogen (3.40%) and potassium content (3.42%).